2023
DOI: 10.1007/s00044-023-03040-y
|View full text |Cite
|
Sign up to set email alerts
|

Recent updates on thienopyrimidine derivatives as anticancer agents

Abstract: Thienopyrimidine derivatives hold a unique place between fused pyrimidine compounds. They are important and widely represented in medicinal chemistry as they are structural analogs of purines. Thienopyrimidine derivatives have various biological activities. The current review discusses different synthetic methods for the preparation of heterocyclic thienopyrimidine derivatives. It also highlights the most recent research on the anticancer effects of thienopyrimidines through the inhibition of various enzymes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 148 publications
0
8
0
Order By: Relevance
“…Melting points were recorded uncorrected using hot-stage melting point equipment from Ernst Leitz Wetzlar, Germany. The 1 H and 13 C-NMR spectra were acquired using a Mercuryplus spectrometer (400 MHz for 1H and 100 MHz for 13C), and chemical shifts were compared with TMS. A Shimadzu QP5050A quadrupolebased mass spectrometer was used to obtain the mass spectra.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Melting points were recorded uncorrected using hot-stage melting point equipment from Ernst Leitz Wetzlar, Germany. The 1 H and 13 C-NMR spectra were acquired using a Mercuryplus spectrometer (400 MHz for 1H and 100 MHz for 13C), and chemical shifts were compared with TMS. A Shimadzu QP5050A quadrupolebased mass spectrometer was used to obtain the mass spectra.…”
Section: Discussionmentioning
confidence: 99%
“…[12] As a result, they, along with several other pyrimidines bearing an annulated five-membered heteroaromatic ring, occupy a unique position among fused pyrimidines. [13] Furthermore, at least three drugs based on the thienopyrimidine scaffold (Figure 1) have been created and tested for anticancer activity by world-renowned pharmaceutical companies such as Genentech, Pyramid, and Sunesis Pharmaceuticals [14,15]. They are already being examined in clinical trials (Phase 1, Phase 1, and Phase 2).…”
Section: Introductionmentioning
confidence: 99%
“…2 illustrates a selection of both marketed VEGFR-2 inhibitors (sunitinib and sorafenib) and previously published pyrazolo [3,4-d]pyrimidine derivatives (I-VI), which have exhibited promising anticancer activity and VEGFR-2 inhibitory effects. 29,[35][36][37][38][39] Building upon these findings and building on our previous research on anticancer derivatives, [40][41][42][43][44][45][46][47] specifically focusing on VEGFR-2 inhibitors, [48][49][50][51][52][53] the main objective of this study was to synthesize novel derivatives of pyrazolo [3,4-d]pyrimidine with anticancer activity, while possessing the fundamental pharmacophoric properties found in first-generation VEGFR-2 inhibitors such as sunitinib, through ring variation and bio isosteric replacement (Fig. 3).…”
Section: Introductionmentioning
confidence: 96%
“…Pictilisib (GDC-0941) and olmutinib, are two well-known thienopyrimidine derivatives that were clinically investigated for treatment of tumours and in cancer therapy. [9] A recent combinatorial virtual screening conducted by Li et al on KRAS G12D inhibitors has revealed that thieno [3,2-d]pyrimidine derivatives are capable of being potential anticancer agents. [10,11] In addition, a recent report by Duan et al, has identified a novel set of thieno [3,2-d]pyrimidines as potent and selective ATR kinase inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…Thieno[3,2‐ d ]pyrimidines, the structural analogues of purines, are being widely studied for their anticancer therapeutic potential and antiproliferative effects on cancer cells. Pictilisib (GDC‐0941) and olmutinib, are two well‐known thienopyrimidine derivatives that were clinically investigated for treatment of tumours and in cancer therapy [9] . A recent combinatorial virtual screening conducted by Li et al .…”
Section: Introductionmentioning
confidence: 99%